2015
DOI: 10.3389/fpls.2015.00095
|View full text |Cite
|
Sign up to set email alerts
|

Response to elevated CO2 in the temperate C3 grass Festuca arundinaceae across a wide range of soils

Abstract: Soils vary widely in mineral nutrient availability and physical characteristics, but the influence of this variability on plant responses to elevated CO2 remains poorly understood. As a first approximation of the effect of global soil variability on plant growth response to CO2, we evaluated the effect of CO2 on tall fescue (Festuca arundinacea) grown in soils representing 10 of the 12 global soil orders plus a high-fertility control. Plants were grown in small pots in continuously stirred reactor tanks in a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…Our finding that the CO 2 effect was enhanced at increasing soil P availability in B. distachyon and M. truncatula supports previous observations that plant growth responses to eCO 2 are lower under nutrient-limited conditions (Poorter and Perez-Soba, 2001; Nord et al , 2015; Pandey et al , 2015 b ), particularly in relation to N supply, which has been more extensively researched than P. The larger growth response to eCO 2 in B. distachyon than in M. truncatula accords with free-air CO 2 enrichment (FACE) studies showing a greater stimulation of photosynthetic C uptake in grasses than in legumes (summarized in Leakey et al , 2009). This would be expected from the long-established, but sometimes overlooked, ‘law of the minimum’ (Liebig, 1843) and more general principles of plant growth-limiting factors (Blackman, 1905).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that the CO 2 effect was enhanced at increasing soil P availability in B. distachyon and M. truncatula supports previous observations that plant growth responses to eCO 2 are lower under nutrient-limited conditions (Poorter and Perez-Soba, 2001; Nord et al , 2015; Pandey et al , 2015 b ), particularly in relation to N supply, which has been more extensively researched than P. The larger growth response to eCO 2 in B. distachyon than in M. truncatula accords with free-air CO 2 enrichment (FACE) studies showing a greater stimulation of photosynthetic C uptake in grasses than in legumes (summarized in Leakey et al , 2009). This would be expected from the long-established, but sometimes overlooked, ‘law of the minimum’ (Liebig, 1843) and more general principles of plant growth-limiting factors (Blackman, 1905).…”
Section: Discussionsupporting
confidence: 91%
“…A reduction in CO 2 efflux with warming may be attributed to interacting factors, such as reduced root respiration and plant C allocation below-ground and/or increased soil moisture controls over heterotrophic respiration (Rustad et al 2001). While we observed a strong coupling of A net and soil respiration, Nord, Jaramillo & Lynch (2015) suggested that the coupling of A net and soil respiration may depend upon soil type and that for many of the most common soil types a change in A net may not necessarily affect soil respiration. The net soil CO 2 efflux rates we collected adjacent to the A. hymenoides target plants are the sum of multiple gross CO 2 fluxes, including root and heterotrophic respiration, and the reduction in the net flux of CO 2 could be related to changes in multiple gross fluxes.…”
Section: Discussioncontrasting
confidence: 50%
“…In fact, this stress combination can severely restrict plant productivity worldwide, as N availability is a limiting factor for plant growth in both natural and agricultural soils in many growth environments (Hirel et al , Nord et al ).…”
Section: Introductionmentioning
confidence: 99%